Innate immunity in cystic fibrosis lung disease - Hartl, Dominik; Mall, Marcus A. (Journal of cystic fibrosis, 2012)
Chronic lung disease determines the morbidity and mortality of cystic ﬁbrosis (CF) patients. The pulmonary immune response in CF is characterized by an early and non-resolving activation of the innate immune system, which is dysregulated at several levels. Here we provide a comprehensive overview of innate immunity in CF lung disease, involving (i) epithelial dysfunction, (ii) pathogen sensing, (iii) leukocyte recruitment, (iv) phagocyte impairment, (v) mechanisms linking innate and adaptive immunity and (iv) the potential clinical relevance. Dissecting the complex network of innate immune regulation and associated pro-inﬂammatory cascades in CF lung disease may pave the way for novel immune-targeted therapies in CF and other chronic infective lung diseases.